Rolling Massage Punggung Berpengaruh Terhadap Pengeluaran ASI Pada Ibu Menyusui - Sari, Niki Winda; Maryati, Syiska Atik; Susilawati, Susilawati (Malang Journal of Midwifery (MAJORY); Vol 2 No 2 (2020): MAJORYDO - 10.31290/majory.v2i2.1744, 2020)
Windasari, Niki. 2020. The influence of back massage massage on the time of breast milk expenditure for breastfeeding mothers in the working area of ??the Cakru puskesmas district. Kencong Kab. Jember Thesis, Main Supervisor: Syiska Atik M., S. SiT., M.Keb . Counselor: Susilawati, S.ST. M.Kes   One effort to reduce IMR is exclusive breastfeeding. Breast milk is the baby's first natural food that provides all the vitamins, minerals and nutrients needed for growth in the first six months, no food or other fluids are needed. Rolling back massage is a technique to provide a relaxing sensation, smooth nerve flow, breast milk channel of both breasts and helps the release of the hormone oxytocin to speed up the time of breastfeeding. The purpose of the study was to determine the effect of back massage on the time of breast milk expenditure in nursing mothers. This type of pre-experimental research uses intact - group comparison design, population of 30 nursing mothers, using purposive sampling techniqueaccording to inclusion criteria, the research instrument used observation sheets and SOPs,The results showed that groups who were given a back massage technique mean value of 11, 93 while groups who were not given back massage with a mean value of 19, 07. This means that given a back massage massage when spending ASI faster than when spending ASI not given a back massage.Analysis of the data with the Mann Whitney test obtained a p value of 0.02, which means that p <0.05 indicates the effect of back massage massage on the timing of ASI release. Based on the results of the study, it was found that the mother in the back massage rolling felt relaxed, comfortable and happy, thus getting out of the hormone oxytocin resulted in a faster time to release milk.   Keywords: Rolling back massage, breast milk.